Chemical Fertilization Alters Soil Carbon in Paddy Soil through the Interaction of Labile Organic Carbon and Phosphorus Fractions - Suphathida Aumtong; Chakrit Chotamonsak; Paweenuch Pongwongkam; Kanchana Cantiya (Agronomy, 2023)
The influence of long-term chemical fertilization in paddy soils is based on the interaction between labile carbon and phosphorus fractions and the manner in which this influences soil organic carbon (SOC). Four soil depths (0–30 cm) were analyzed in this study. Easily oxidized organic carbon components, such as permanganate oxidized carbon (POXC) and dissolved organic carbon (DOC), and other physicochemical soil factors were evaluated. The correlation and principal component analyses were used to examine the relationship between soil depth and the parameter dataset. The results showed that Fe-P concentrations were greater in the 0–5 cm soil layer. DOC, inorganic phosphate fraction, and other soil physiochemical characteristics interacted more strongly with SOC in the 0–5 cm soil layer, compared to interactions in the 10–15 cm layer, influencing soil acidity. An increase in DOC in the 0–5 cm soil layer had a considerable effect on lowering SOC, consistent with P being positively correlated with POXC, but negatively with SOC and water-soluble carbon (WSC). The changes in SOC could be attributed to the relationship between DOC and inorganic phosphate fractions (such as Fe-P) under specific soil pH conditions. An increase in soil DOC could be caused by changes in the P fraction and pH. The DOC:Avai. P ratio could serve as a compromise for the C and P dynamic indicators. The soil depth interval is a critical element that influences these interactions. Agricultural policy and decision-making may be influenced by the P from chemical fertilization practices, considering the yields and environmental effects.